Qualidade fisiológica de sementes de soja em função da danificação mecânica - Rigo, Geliandro Anhaia (2013)
This study aimed to evaluate the physiological quality of soybean seeds damaged at different levels as well as the effect of seed treatment with fungicide after 150 days of storage. Used - if seeds of the cultivar Turbo. These seeds were harvested and threshed manually to ensure that there were no initial mechanical damage. Damage to seeds used a mechanical damaging, "Impact Test". Seeds were individually exposed on a counter seed round hole for receiving the impact through a 100 g weight at different heights (A1 = A2 = 10 cm and 20 cm), adding three levels of damage without damage, moderately damaged and highly damaged. Done that seeds were packaged in paper bags Derosal Plus fungicide treated and stored in BOD with temperature 22 ° C ± 3 ° C, for further evaluation of vigor at 30, 60, 90, 120 and 150 days of storage. The tests were performed, germination, first count of germination and accelerated aging. Results were subjected to analysis of variance and mean comparison by Scott Knott test at 5% using the statistical program Assistat. Highly damaged soybean seeds by 50% reduces your potential germination in 150 days of storage under controlled conditions of 22 ° C ± 3 ° C and relative humidity of 60%.The fungal treatment with Derosal Plus in soybean seeds reduces the process of deterioration during storage.